(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2022)
Obesity in Indonesia, especially experienced by adolescents aged 16-18 years, has increased nationally with a prevalence of 7.3%. Consumption of snacks with sufficient fiber and antioxidant content can be an effort to overcome obesity. Flaky crackers are one of the most common snacks consumed in Indonesia. This study aims to examine the effect of purple sweet potato flour substitution on high fiber and antioxidant flaky crackers for adolescents. The research was conducted from November-December 2020 and March-April 2021. The level of purple sweet potato flour were F1(10%), F2(20%), F3(30%), and F4(40%). The results showed that flaky crackers with the highest purple sweet potato flour substitution (F4:40%) were the chosen formula with the best acceptability and nutritional content. F4 flaky crackers were claimed to be high in fiber with a fiber content of 10.8 g in 100 g of product. The energy content of F4 flaky crackers per serving size (216 kcal) meets 10% of the energy needs of adolescents aged 16-18 years.